2019
DOI: 10.3389/fpsyg.2019.00190
|View full text |Cite
|
Sign up to set email alerts
|

Do Chinese Teachers Perform Emotional Labor Equally? Multi-Group Comparisons Across Genders, Grade Levels and Regions

Abstract: The emotional aspects of teaching are important and teachers’ emotional labor, or, how teachers manage emotions at school, has been attracting more and more attention recently. Using multi-group structural equation modeling, this study investigated the measurement invariance of, and the relationships between, teachers’ emotional labor strategies and teaching satisfaction. Participants included teachers from primary and secondary schools in Hong Kong and mainland China. Three sets of group comparisons have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“…Estos resultados no son congruentes con algunas investigaciones que confirman diferencias de género en algunas dimensiones de IER como adaptación a los cambios y automotivación a favor de las profesoras (Cejudo y López-Delgado, 2017). Del mismo modo, estudios anteriores evidencian diferencias de género en la satisfacción laboral a favor de las profesoras (Huang et al, 2019;Nieto y Riveiro, 2006). Posiblemente, nuestros resultados estén influidos por la descompensación en la muestra en cuanto a profesores y profesoras, hubiera sido necesario equiparar la muestra en cuenta a mujeres y hombres como realizan otros estudios (p.ej., Antoniou et al, 2006).…”
Section: Discussionunclassified
“…Estos resultados no son congruentes con algunas investigaciones que confirman diferencias de género en algunas dimensiones de IER como adaptación a los cambios y automotivación a favor de las profesoras (Cejudo y López-Delgado, 2017). Del mismo modo, estudios anteriores evidencian diferencias de género en la satisfacción laboral a favor de las profesoras (Huang et al, 2019;Nieto y Riveiro, 2006). Posiblemente, nuestros resultados estén influidos por la descompensación en la muestra en cuanto a profesores y profesoras, hubiera sido necesario equiparar la muestra en cuenta a mujeres y hombres como realizan otros estudios (p.ej., Antoniou et al, 2006).…”
Section: Discussionunclassified
“…Huang at al. [ 24 ] defined emotional labor as one’s personal control over their emotions to control the facial and physical expressions that can be seen by others. Moreover, emotional labor has exchange value and can be sold for wages.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…This is consistent with previous studies ( 40 , 41 ). A possible explanation is that females are more likely to express their emotional distress, are more sensitive to stress, and are more vulnerable to negative emotions than males ( 42 44 ). Multivariable analysis showed that daily sleep time was an influencing factor in job burnout among male dental postgraduates; the longer the daily sleep time, the lower the risk of job burnout.…”
Section: Discussionmentioning
confidence: 99%